Review Article: Lung Cancer Pathophysiology using CRISPR Technology - Mohammed Subhi Mohammed; Rana Ahmed Najm; Ameer Ali Imarah (International Journal for Research in Applied Sciences and Biotechnology, 2021)
According to the World Health Organization, respiratory disorders, such as “influenza infection, acute tracheal bronchitis, TB, chronic obstructive pulmonary disease, lung cancer, and nasopharyngeal carcinoma”, have a major influence on human health. While environmental and socioeconomic variables might impact the pathogenesis of lung and respiratory tract diseases, it is nevertheless important to further investigate genetic and epigenetic reasons since a great many respiratory illnesses have a genetic or epigenetic basis. CRISPR is made up of interspaced, regularly-spaced palindromic repeated sequences and related proteins that carry out the CRISPR system's duties, which are found in prokaryotes' immune systems. This technology may be used to target, alter, and control genes, making it essential in respiratory research. Cas9 systems enable preclinical modelling of causative variables implicated in respiratory disorders, to generate fresh insights into its operations. CRISPR is also used to hunt for respiratory functions and pathology-associated genes. Which may lead to the discovery of new disease causes or therapeutic targets. The genetic and epigenetic mutations and the disease-associated mutations could be edited using CRISPR/Cas9. This kind of personalised medicine, which might be combined with stem cell reprogramming and transplantation are additional methods, that support embryonic stem cell expansion, might lead to the creation of novel respiratory illness treatment options. The new and developing area of investigation of CRISPR gene editing is one that requires further study the challenges of its specialty and the need for effective and safe delivery strategies. In respiratory health research and treatment, CRISPR systems represent an important step forward, and the discoveries made possible by this technology are likely to continue.